Handmade endoloop knotting technique without knot pusher for appendicular stump closure in laparoscopic appendectomy- personal experience (Bangladesh Journal of Medical Science, 2018)
Aim: to devises a handmade endoloop knotting technique without the use of knot pusher thereby reducing the overall cost of laparoscopic appendectomy.Material and methods: This prospective study was conducted in MMIMSR Ambala from January 2015 to august 2017. All operations were performed by the same surgical team. Mesoappendix was coagulated with bipolar cautery and cut with scissors. Two handmade Meltzer loops were placed on base of appendix and tightened using conventionalgraspers.Results: 53 patients were included in the study. The time spent for preparing and tyingone loop was approximately 20-25 seconds. None of the patients had leakage from the appendicular stump. Only one polyglactin suture was used to make three loops. Knot pusher was not used in any of the patients.Conclusion: handmade endoloop used in this prospective study for securing appendicular stump using conventional laparoscopic graspers was found to be equally safe and can be easily mastered by any laparoscopic surgeon, which will reduce his dependency upon preformed endoloops making the procedure cost effective.Bangladesh Journal of Medical Science Vol.17(2) 2018 p.255-257